2013
DOI: 10.4025/actascitechnol.v35i4.20251
|View full text |Cite
|
Sign up to set email alerts
|

<b>Chemical characterization of pressed and refined licuri (<i>Syagrus coronata</i>) oils</b> - doi: 10.4025/actascitechnol.v35i4.20251

Abstract: ABSTRACT. Knowing the composition of foods is fundamental to assess their potentialities and the availability of nutrients to consuming populations. The objective of this work was to increase knowledge about the licuri fruit (Syagrus coronata) by quantifying the fatty acids and verifying the antioxidant potential in the kernel´s fruit and in the pressed oil´s fruit. The lipid profile data shows a predominance of saturated fats, high levels of medium-chain fatty acids such as lauric and myristic fatty acids, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…This study demonstrated that S. coronata seed oil is a rich source of medium-chain fatty acids, which could be suitable for biomedical applications (cosmetic and pharmaceutical industries), as showed by Leal et al (2013). Our data are in agreement with the work of Bauer et al (2013), which showed that saturated fats with high levels of medium-chain fatty acids (such as lauric and myristic fatty acids) are prevalent in kernel and fruit oil of S. coronata collected in Bahia, Brazil. These authors commented that this composition is very similar to coconut oil.…”
Section: Discussionsupporting
confidence: 89%
“…This study demonstrated that S. coronata seed oil is a rich source of medium-chain fatty acids, which could be suitable for biomedical applications (cosmetic and pharmaceutical industries), as showed by Leal et al (2013). Our data are in agreement with the work of Bauer et al (2013), which showed that saturated fats with high levels of medium-chain fatty acids (such as lauric and myristic fatty acids) are prevalent in kernel and fruit oil of S. coronata collected in Bahia, Brazil. These authors commented that this composition is very similar to coconut oil.…”
Section: Discussionsupporting
confidence: 89%
“…that may have played a role in the lower intake associated with dietary licuri. High concentrations of MCFAs has been reported for licuri [4]. The MCFA have physical properties (lower melting point) similar to unsaturated fatty acids, which increase cellular membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a 17% inclusion of licuri has been reported to improve feed conversion and to increase ADG [3], and no changes in the dry matter intake (DMI) of lambs was observed with 16% inclusion of licuri cake [1]. In addition, the fatty acid profile of licuri oil is different from traditional oil sources; it is highly saturated, with high percentages of medium chain fatty acids (MCFA), mainly lauric and myristic acids [4]. Fat is commonly used to increase the energy density in animal diets; thus, licuri may be used for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils are those obtained from parts of plants, such as seeds, nuts, flowers and fruit pulp, and vegetables and legumes mainly formed by lipids. They are the most produced have a high amount of antioxidant compounds [7 -9] and palm kernel oil has a large amount of saturated fatty acids [10,11]. These different compositions allow vegetable oils to be applied to various products.…”
Section: Introductionmentioning
confidence: 99%